MEDIA KOMUNIKASI VISUAL UNTUK MENUNJANG PROMOSI DI INSTITUT AGAMA HINDU NEGERI GDE PUDJA MATARAM - Ida Bagus Yuda Phalguna (IAHN Gde Pudja Mataram, 2022)
The rapid advancement of media in visual media in this era is very supportive in communication needs. In life it is often the medium of visual communication that supports the development of less efficient and effective promotion. In the current situation, so many public religious colleges are still rigid in luring freshmen. Communication intermediary tools in visuals can be implemented by religious universities, especially Hinduism, in introducing and increasing prestige to provide interesting news to new students in 2022. What was found in this case was the effectiveness of promotional media in disseminating information, or inviting prospective new students to make the religious campus known to the wider community. The way of writing presented to assess the progress of existing promotional media is real and even used to this day, such as banners, brochures, billboards, banners and social media communications. The conclusions in particular of this journal are considered effective and make a very consistent contribution. This writing provides an opportunity to improve the quality of promotion with promotional media that is often used, namely digital marketing media for state religious universities through appropriate steps that can be accepted by the wider community. To produce several forms of promotional media that can account for what has been given to the wider community, management is needed in accordance with the problem so that it can overcome the problem at hand.